2012
DOI: 10.1177/0018720811428734
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Apparent Latency on Simulator Sickness While Using a See-Through Helmet-Mounted Display

Abstract: Potential applications include HMD use in which head position is tracked and visual imagery is linked to head or body movement, such as in virtual and augmented reality systems, and is thus critical to functionality and performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Moreover, latency can disturb the user performance and cause simulator sickness (Steed, 2008). Predictive compensation can be utilized to reduce apparent latency, resulting in a lower magnitude of simulator sickness (Buker et al, 2012).…”
Section: How Latency Influences Effectiveness Of Training Systemsmentioning
confidence: 99%
“…Moreover, latency can disturb the user performance and cause simulator sickness (Steed, 2008). Predictive compensation can be utilized to reduce apparent latency, resulting in a lower magnitude of simulator sickness (Buker et al, 2012).…”
Section: How Latency Influences Effectiveness Of Training Systemsmentioning
confidence: 99%
“…According to various studies, in virtual environments, high-latency that can result from low frame rates can lead to reduced sense of presence [55], impaired task performance, reduced user response [56][57] or simulator sickness [58]. It has been determined by some authors [59] that the critical end-to-end latency is at 17ms, but other authors [60] found this threshold to be even lower.…”
Section: Cyber Sickness -Symptoms Causes and Outcomesmentioning
confidence: 99%
“…When latency increases, the user experiences decreased visual acuity, decreased performance, decreased presence and is less susceptible to training [18]. Increased latency is also associated with increased levels of simulator sickness [19]. Stress effects also increase with added latency [20].…”
Section: Effects Of Latencymentioning
confidence: 99%